2023
DOI: 10.1111/jog.15742
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and stress urinary incontinence: The risk factors of stress urinary incontinence in perimenopausal and postmenopausal women

Abstract: ObjectiveThe prevalence of stress urinary incontinence (SUI) increases around menopause. The quality of life of perimenopausal and postmenopausal women with SUI is significantly affected. This study aimed to investigate the prevalence of SUI and the associated risk factors in a population of Chinese perimenopausal and postmenopausal women.MethodsA total of 273 perimenopausal and postmenopausal women were enrolled, and a cross‐sectional study was conducted. SUI was defined as an involuntary loss of urine with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…63 A cross-sectional study of perimenopausal and postmenopausal women reported a correlation between climacteric symptoms associated with menopause and stress UI. 64 In contrast, a longitudinal study of midlife and older women found no association between menopause and the incidence or remission of UI. 65 Only one study included in this review explicitly reported current menopause status of participants.…”
Section: Discussionmentioning
confidence: 95%
“…63 A cross-sectional study of perimenopausal and postmenopausal women reported a correlation between climacteric symptoms associated with menopause and stress UI. 64 In contrast, a longitudinal study of midlife and older women found no association between menopause and the incidence or remission of UI. 65 Only one study included in this review explicitly reported current menopause status of participants.…”
Section: Discussionmentioning
confidence: 95%